A domino reaction strategy for facile and modular construction of synthetically challenging functionalized ortho-fluoroanilines - Grau, Benedikt; Kohlbauer, Sascha; Gu, Yun Gyeong; Hahn, Friedrich; Lösing, Josephine; Wangen, Christina; Stangier, Maximilian; Ackermann, Lutz; Marschall, Manfred; Tsogoeva, Svetlana (Organic Chemistry Frontiers, 2024)
The selective formation of ortho-fluoroanilines, representing versatile intermediates for the pharmaceutical and fine chemical industries, relies to date on, e.g., transition-metal-catalyzed fluorination of azobenzenes, which must be preformed from aniline derivatives. While few efficient methods for aniline synthesis were reported, sustainable, straightforward, and selective synthesis of fluoroanilines, and in particular ortho-fluoroanilines, remains challenging. Herein, we describe a domino approach that involves the simultaneous construction of a benzene ring and the installation of both amine and fluorine groups in a single operation under metal-free conditions, starting from readily available acyclic compounds. The developed atom- and cost-efficient, highly convenient, selective, and environmentally friendly four-step domino process allows the formation of a variety of functionalized ortho-fluoroanilines with yields of up to 80% and bypasses the selectivity issues of transition-metal-catalyzed aniline fluorination reactions. Furthermore, we show that the new domino products can efficiently be utilized to synthesize fluorinated azo dye and (tetrahydro)quinazoline derivatives in a bioactive form, i.e., possessing a first-time proven micromolar antiviral activity and high selectivity (EC50 (HCMV) down to 1.9 ± 0.7 μM, CC50 up to >100 μM), under conventional and/or visible-light mediated conditions.
CRIS-Team Scopus Importer:2024-10-25

An antiviral targeting strategy based on the inducible interference with cytomegalovirus nuclear egress complex - Kicuntod, Jintawee; Häge, Sigrun; Lösing, Josephine; Kopar, Serli; Muller, Yves; Marschall, Manfred (Antiviral Research, 2023)
The nucleocytoplasmic capsid egress of herpesviruses like the human cytomegalovirus (HCMV) is based on a uniquely regulated process. The core nuclear egress complex (NEC) of HCMV, represented by the pUL50–pUL53 heterodimer, is able to oligomerize and thus to build hexameric lattices. Recently, we and others validated the NEC as a novel target for antiviral strategies. So far, the experimental targeting approaches included the development of NEC-directed small molecules, cell-penetrating peptides and NEC-directed mutagenesis. Our postulate states that an interference with the hook-into-groove interaction of pUL50–pUL53 prevents NEC formation and strictly limits viral replication efficiency. Here, we provide an experimental proof-of-concept of the antiviral strategy: the inducible intracellular expression of a NLS-Hook-GFP construct exerted a pronounced level of antiviral activity. The data provide evidence for the following points: (i) generation of a primary fibroblast population with inducible NLS-Hook-GFP expression showed nuclear localization of the construct, (ii) interaction between NLS-Hook-GFP and the viral core NEC was found specific for cytomegaloviruses but not for other herpesviruses, (iii) construct overexpression exerted a strong antiviral activity against three strains of HCMV, (iv) confocal imaging demonstrated the interference with NEC nuclear rim formation in HCMV-infected cells, and (v) quantitative nuclear egress assay confirmed the block of viral nucleocytoplasmic transition and, consequently, an inhibitory effect onto viral cytoplasmic virion assembly complex (cVAC). Combined, data confirmed that the specific interference with protein-protein interaction of the HCMV core NEC represents an efficient antiviral targeting strategy.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Antiviral proof-of-concept; Cytomegalovirus infection; Efficient interference with viral replication; Hook-into-groove principle; Inducible NLS-Hook-GFP expression; Major human pathogen; Novel drug targeting options; Nuclear egress-based antiviral strategy

Cyclin-Dependent Kinase 8 Represents a Positive Regulator of Cytomegalovirus Replication and a Novel Host Target for Antiviral Strategies - Obergfäll, Debora; Wild, Markus; Sommerer, Mona; Barillas Dahm, Malena; Kicuntod, Jintawee; Tillmanns, Julia; Kögler, Melanie; Lösing, Josephine; Dhotre, Kishore; Müller, Regina; Wangen, Christina; Wagner, Sabrina; et al. (Pharmaceutics, 2024)
Background. Cyclin-dependent kinase 8 (CDK8) is a multifaceted regulator and represents a catalytic component of the transcriptional Mediator complex. CDK8 activity, on the one hand, increases transcriptional elongation by the recruitment of Mediator/super elongation complexes, but, on the other hand, negatively regulates CDK7-controlled transcriptional initiation through inactivating cyclin H phosphorylation. Recently, these combined properties of CDK8 have also suggested its rate-limiting importance for herpesviral replication. Objectives. In this paper, we focused on human cytomegalovirus (HCMV) and addressed the question of whether the pharmacological inhibition or knock-down of CDK8 may affect viral replication efficiency in cell culture models. Methods. A number of human and animal herpesviruses, as well as non-herpesviruses, were used to analyze the importance of CDK8 for viral replication in cell culture models, and to assess the antiviral efficacy of CDK8 inhibitors. Results. Using clinically relevant CDK8 inhibitors (CCT-251921, MSC-2530818, and BI-1347), HCMV replication was found strongly reduced even at nanomolar drug concentrations. The EC50 values were consistent for three different HCMV strains (i.e., AD169, TB40, and Merlin) analyzed in two human cell types (i.e., primary fibroblasts and astrocytoma cells), and the drugs comprised a low level of cytotoxicity. The findings highlighted the following: (i) the pronounced in vitro SI values of anti-HCMV activity obtained with CDK8 inhibitors; (ii) a confirmation of the anti-HCMV efficacy by CDK8–siRNA knock-down; (iii) a CDK8-dependent reduction in viral immediate early, early, and late protein levels; (iv) a main importance of CDK8 for viral late-stage replication; (v) several mechanistic aspects, which point to a strong impact on viral progeny production and release, but a lack of CDK8 relevance for viral entry or nuclear egress; (vi) a significant anti-HCMV drug synergy for combinations of inhibitors against host CDK8 and the viral kinase vCDK/pUL97 (maribavir); (vii) finally, a broad-spectrum antiviral activity, as seen for the comparison of selected α-, β-, γ-, and non-herpesviruses. Conclusions. In summary, these novel data provide evidence for the importance of CDK8 as a positive regulator of herpesviral replication efficiency, and moreover, suggest its exploitability as an antiviral target for novel strategies of host-directed drug development.
CRIS-Team Scopus Importer:2024-10-04
Keywords: antiviral approach with CDK8-inhibitory small molecules; broad-spectrum antiviral CDK8 inhibitors; cyclin-dependent kinase 8 (CDK8); human cytomegalovirus (HCMV); human pathogenic herpesviruses; negative impact of CDK8 inhibitors; novel host-directed targeting strategies; regulation of viral replication; siRNA-mediated CDK8 knock-down; virus-supportive cellular protein kinases

‘Getting Better’—Is It a Feasible Strategy of Broad Pan-Antiherpesviral Drug Targeting by Using the Nuclear Egress-Directed Mechanism? - Tillmanns, Julia; Kicuntod, Jintawee; Lösing, Josephine; Marschall, Manfred (International Journal of Molecular Sciences, 2024)
The herpesviral nuclear egress represents an essential step of viral replication efficiency in host cells, as it defines the nucleocytoplasmic release of viral capsids. Due to the size limitation of the nuclear pores, viral nuclear capsids are unable to traverse the nuclear envelope without a destabilization of this natural host-specific barrier. To this end, herpesviruses evolved the regulatory nuclear egress complex (NEC), composed of a heterodimer unit of two conserved viral NEC proteins (core NEC) and a large-size extension of this complex including various viral and cellular NEC-associated proteins (multicomponent NEC). Notably, the NEC harbors the pronounced ability to oligomerize (core NEC hexamers and lattices), to multimerize into higher-order complexes, and, ultimately, to closely interact with the migrating nuclear capsids. Moreover, most, if not all, of these NEC proteins comprise regulatory modifications by phosphorylation, so that the responsible kinases, and additional enzymatic activities, are part of the multicomponent NEC. This sophisticated basis of NEC-specific structural and functional interactions offers a variety of different modes of antiviral interference by pharmacological or nonconventional inhibitors. Since the multifaceted combination of NEC activities represents a highly conserved key regulatory stage of herpesviral replication, it may provide a unique opportunity towards a broad, pan-antiherpesviral mechanism of drug targeting. This review presents an update on chances, challenges, and current achievements in the development of NEC-directed antiherpesviral strategies.
CRIS-Team Scopus Importer:2024-03-22
Keywords: core and multicomponent NEC extensions; cytomegalovirus (HCMV); essential steps of viral replication; human pathogenic herpesviruses; NEC-directed mode of action; novel antiviral drug targeting; nuclear egress complex (NEC); strategies of antiviral drug development; viral nucleocytoplasmic capsid egress

'Shared-Hook' and 'Changed-Hook' Binding Activities of Herpesviral Core Nuclear Egress Complexes Identified by Random Mutagenesis - Lösing, Josephine; Haege, Sigrun; Schütz, Martin; Wagner, Sabrina; Wardin, Julia; Sticht, Heinrich; Marschall, Manfred (Cells, 2022)
Herpesviruses replicate their genomes and assemble their capsids in the host cell nucleus. To progress towards morphogenesis in the cytoplasm, herpesviruses evolved the strategy of nuclear egress as a highly regulated process of nucleo-cytoplasmic capsid transition. The process is conserved among alpha-, beta- and gamma-herpesviruses and involves the formation of a core and multicomponent nuclear egress complex (NEC). Core NEC is assembled by the interaction between the nucleoplasmic hook protein, i.e., pUL53 (human cytomegalovirus, HCMV), and the integral membrane-associated groove protein, i.e., pUL50. Our study aimed at the question of whether a panherpesviral NEC scaffold may enable hook-into-groove interaction across herpesviral subfamilies. For this purpose, NEC constructs were generated for members of all three subfamilies and analyzed for multi-ligand interaction using a yeast two-hybrid (Y2H) approach with randomized pUL53 mutagenesis libraries. The screening identified ten library clones displaying cross-viral shared hook-into-groove interaction. Interestingly, a slightly modified Y2H screening strategy provided thirteen further changed-hook pUL53 clones having lost parental pUL50 interaction but gained homolog interaction. In addition, we designed a sequence-predicted hybrid construct based on HCMV and Epstein-Barr virus (EBV) core NEC proteins and identified a cross-viral interaction phenotype. Confirmation was provided by applying protein-protein interaction analyses in human cells, such as coimmunoprecipitation settings, confocal nuclear rim colocalization assays, and HCMV Delta UL53 infection experiments with pUL53-complementing cells. Combined, the study provided the first examples of cross-viral NEC interaction patterns and revealed a higher yield of human cell-confirmed binding clones using a library exchange rate of 3.4 than 2.7. Thus, the study provides improved insights into herpesviral NEC protein binding specificities of core NEC formation. This novel information might be exploited to gain a potential target scaffold for the development of broadly acting NEC-directed inhibitory small molecules.
CRIS-Team WoS Importer:2023-01-27

The crystal structure of the varicella-zoster Orf24-Orf27 nuclear egress complex spotlights multiple determinants of herpesvirus subfamily specificity - Schweininger, Johannes; Kriegel, Mark; Häge, Sigrun; Conrad, Marcus; Alkhashrom, Sewar; Lösing, Josephine; Weiler, Sigrid; Tillmanns, Julia; Egerer-Sieber, Claudia; Decker, Andrea; Rovis, Tihana Lenac; Eichler, Jutta; et al. (Journal of Biological Chemistry, 2022)
Varicella-zoster virus (VZV) is a human pathogen from the α-subfamily of herpesviruses. The VZV Orf24-Orf27 complex represents the essential viral core nuclear egress complex (NEC) that orchestrates the egress of the preassembled virus capsids from the nucleus. While previous studies have primarily emphasized that the architecture of core NEC complexes is highly conserved among herpesviruses, the present report focuses on subfamily-specific structural and functional features that help explain the differences in the autologous versus nonautologous interaction patterns observed for NEC formation across herpesviruses. Here, we describe the crystal structure of the Orf24-Orf27 complex at 2.1 Å resolution. Coimmunoprecipitation and confocal imaging data show that Orf24-Orf27 complex formation displays some promiscuity in a herpesvirus subfamily-restricted manner. At the same time, analysis of thermodynamic parameters of NEC formation of three prototypical α-, β-, and γ herpesviruses, i.e., VZV, human cytomegalovirus (HCMV), and Epstein-Barr virus (EBV), revealed highly similar binding affinities for the autologous interaction with specific differences in enthalpy and entropy. Computational alanine scanning, structural comparisons, and mutational data highlight intermolecular interactions shared among α-herpesviruses that are clearly distinct from those seen in β- and γ-herpesviruses, including a salt bridge formed between Orf24-Arg167 and Orf27-Asp126. This interaction is located outside of the hook-into-groove interface and contributes significantly to the free energy of complex formation. Combined, these data explain distinct properties of specificity and permissivity so far observed in herpesviral NEC interactions. These findings will prove valuable in attempting to target multiple herpesvirus core NECs with selective or broadacting drug candidates.
CRIS-Team Scopus Importer:2022-03-04